1971
DOI: 10.1017/s002202990001949x
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of unsaturated oils given to dairy cows with rations of different roughage content

Abstract: SummaryThree experiments were conducted to determine the effect of feeding polyunsaturated fish oils to dairy cows receiving rations of high, medium or low roughage content. In the rumen, the decreases in the proportion of acetic acid and increases in propionic acid induced by the oils became greater as the amount of oil given was increased but the magnitude of the response to any dose depended upon the composition of the basal diet. The effects on volatile fatty acids (VFA) proportions of small amounts of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

1975
1975
2004
2004

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…These differences in VFA concentrations were probably related to differences in rumen volume rather than to a disturbance in rumen fermentation, because no concomitant effects on fibre digestion were observed. In contrast to the results presented in the present paper, other studies have generally reported that inclusion of either linseed oil (Ikwuegbu & Sutton, 1982;Broudiscou et al 1994) or fish oil (Nicholson & Sutton, 1971) increases the production of propionate in the rumen. This increased production of propionate is elicited by changes in the species composition of rumen microbes, with unsaturated fatty acids being toxic to cellulolytic and methanogenic bacteria (Demeyer & Van Nevel, 1995).…”
Section: Rumen Metabolismcontrasting
confidence: 99%
“…These differences in VFA concentrations were probably related to differences in rumen volume rather than to a disturbance in rumen fermentation, because no concomitant effects on fibre digestion were observed. In contrast to the results presented in the present paper, other studies have generally reported that inclusion of either linseed oil (Ikwuegbu & Sutton, 1982;Broudiscou et al 1994) or fish oil (Nicholson & Sutton, 1971) increases the production of propionate in the rumen. This increased production of propionate is elicited by changes in the species composition of rumen microbes, with unsaturated fatty acids being toxic to cellulolytic and methanogenic bacteria (Demeyer & Van Nevel, 1995).…”
Section: Rumen Metabolismcontrasting
confidence: 99%
“…mol VFA produced/kg organic matter fermented in the rumen = 13 (Sutton, 1971); mol ATP produced/mol VFA = 2-3 (Hungate, 1966); microbial dry matter produced (g)/mol ATP = 10-5 (Bauchop & Elsden, 1960); microbial true protein (g)/g microbial dry matter = 0-6 (Gunsalus & Shuster, 1961).…”
Section: Discussionmentioning
confidence: 99%
“…TNTTROT)TTPTTO"Nr reasonable accuracy by determination of the apparent digestion of energy in the stomach (Nicholson Many attempts have been made to improve food & Sutton, 1969;Sutton, 1971). For protein and utilization by ruminants by the use of various lipids it is important to know the amount of their additives, but there is little information about the net microbial synthesis as well as the true digestion effect of such treatments on the digestion of food of these components of the food and measurement or synthesis of microbial products in the rumen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from several laboratories (Cottyn et al, 1972;Smith et al, 1968;Nicholson and Sutton, 1971;Robertson and Hawke, 1964)indicated the addition of 2.5 to 5% oil decreased the amount of acetic acid and increased the amount of propionic acid in rumen fluid. Also McDonald et al (1965) indicated that urea increased VFA concentration in lambs fed semi-purified diets.…”
Section: Resultsmentioning
confidence: 99%